2013
DOI: 10.1097/id.0b013e3182920dc5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Definitive Casts Using 4 Implant-Level Impression Techniques in a Scenario of Multi-Implant System With Different Implant Angulations and Subgingival Alignment Levels

Abstract: PURPOSE: To evaluate the effect of various implant-level impression techniques on the accuracy of definitive casts for a multiple internal connection implant system with different implant angulations and subgingival depths. MATERIAL AND METHODS: Six tapered Screw-Vent implants were placed in a reference model with different angles (0, 15, and 30 degrees) and subgingival positions (0, 1, and 3 mm). Twenty medium-consistency polyether impressions of this model were made with 4 techniques (n = 5 per group): (1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 29 publications
(85 reference statements)
6
46
1
Order By: Relevance
“…These findings are in agreement with several studies which reported the superiority of the splinted technique for internal connection implants. [11][12][13][14][15][16][17] Moreover, regarding implant angulation, 3 in vitro investigations showed that the splinted technique was more accurate than the nonsplinted technique for making an impression of angulated implants. 5,7,16 Some authors, however, have found no significant differences in the accuracy of internal connection implant impressions with the splinted and nonsplinted techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are in agreement with several studies which reported the superiority of the splinted technique for internal connection implants. [11][12][13][14][15][16][17] Moreover, regarding implant angulation, 3 in vitro investigations showed that the splinted technique was more accurate than the nonsplinted technique for making an impression of angulated implants. 5,7,16 Some authors, however, have found no significant differences in the accuracy of internal connection implant impressions with the splinted and nonsplinted techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Moreover, regarding implant angulation, 3 in vitro investigations showed that the splinted technique was more accurate than the nonsplinted technique for making an impression of angulated implants. 5,7,16 Some authors, however, have found no significant differences in the accuracy of internal connection implant impressions with the splinted and nonsplinted techniques. [18][19][20][21] The conflicting findings in the literature concerning the most accurate impression technique might be explained by the different study designs and implant systems used, the different impression and splinting materials, the inaccurate repositioning of the impression copings, the various angulations of the implants, and the variable dental stone expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these impression techniques are generally used for transferring implant position to the final cast in dental practice . Comparing the square and conical transfer impression copings in different implant systems has been addressed in the literature . Some studies showed that the indirect impression technique (transfer) created a more accurate working cast compared with the direct techniques (pick‐up) .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in this experiment, the exact position of the implants were not attained in any of the impression methods. (15) This shows that the exact fit of the superstructure might be unattainable. Since the exact acceptable amount of misfit frame and rack on several implants are not determined, it is possible to define the discrepancy amount of less than 30 µ , which is not detectible clinically, as the reference to accept or reject the fit frame and rack.…”
Section: Discussionmentioning
confidence: 99%